Tanggungjawab Perusahaan Atas Perbuatan Karyawan Yang Mengakibatkan Kerugian Terhadap Orang Lain (Studi Putusan NO. 206/PDT/2014/PT.SBY)” - Mhd. Arief Akbar Surahman (Iuris Studia: Jurnal Kajian Hukum, 2021)
Article 1367 of the Civil Code is the main basis for the (indirect) responsibility of employers (employers) for unlawful acts in the context of work. According to this doctrine of respondeat superior, an entrepreneur is responsible for unlawful acts committed by his employees or employees if the employee acts within the scope of carrying out his work or within the scope of his work. The type of research used in this research is normative juridical research. The nature of this research is descriptive analytical. The results of the discussion in this study are related to legal arrangements for the employer's responsibility for unlawful acts committed by employees. In filing a lawsuit or claim for compensation, the injured party or the plaintiff must be able to prove the facts against the unlawful act committed by the defendant and/or co-defendant so that it can be said that the person committed an unlawful act which because the act caused harm to the plaintiff there was a relationship In addition to that, it must also be proven that there is an error in the perpetrator or the perpetrator related to this matter, based on article 1367 of the Civil Code, the company is responsible for the losses that arise and must be sued before a judge. Accountability for errors based on Article 1365 of the Civil Code. Meanwhile, public transportation companies and vehicle owners are responsible for unlawful acts committed by their employees responsibly based on Article 1367 of the Civil Code and Article 234 of the UULAJ due to the relationship between employer and subordinate. or the Vicarios Liability doctrine, the panel of judges has rendered a decision in accordance with the applicable regulations in case no. 206/PDT/2014/PT.SBY by implementing the accountability of public transport companies and their owners